Association between general and central adiposity in childhood, and change in these, with cardiovascular risk factors in adolescence: prospective cohort study. (25th November 2010) - Lawlor, Debbie A; Benfield, Li; Logue, Jennifer; Tilling, Kate; Howe, Laura D; Fraser, Abigail; Cherry, Lynne; Watt, Pauline; Ness, Andrew R; Davey Smith, George; Sattar, Naveed
Abstract : Objectives To examine the prospective associations between body mass index (BMI), waist circumference, and fat mass in childhood and cardiovascular risk factors at age 15-16. Design Prospective cohort study. Setting Avon Longitudinal Study of Parents and Children. Participants 5235 children aged 9-12 at start of study. Main exposures BMI, waist circumference, and fat mass determined by dual energy x ray absorptiometry, assessed at age 9-12 and at age 15-16. Main outcome measures Systolic and diastolic blood pressure and concentrations of fasting glucose, insulin, triglycerides, low density lipoprotein cholesterol, and high density lipoprotein cholesterol assessed at age 15-16. Results In girls a 1 SD greater BMI at age 9-12 was associated with cardiovascular risk factors at age 15-16 in fully adjusted models: odds ratio 1.23 (95% confidence interval 1.10 to 1.38) for high systolic blood pressure (≥130 mm Hg); 1.19 (1.03 to 1.38) for high concentration of low density lipoprotein cholesterol (≥2.79 mmol/l); 1.43 (1.06 to 1.92) for high concentration of triglycerides (≥1.7 mmol/l); 1.25 (1.08 to 1.46) for low concentration of high density lipoprotein cholesterol (<1.03 mmol/l); and 1.45 (1.22 to 1.73) for high concentration of insulin (≥16.95 IU/l). Equivalent results in boys were 1.24 (1.13 to 1.37) for systolic blood pressure; 1.30 (1.07 to 1.59) for low density lipoprotein cholesterol; 1.96 (1.51 to 2.55) for triglycerides; 1.39 (1.22 to 1.57) for high density lipoprotein cholesterol, and 1.84 (1.56 to 2.17) for insulin. BMI was associated with high fasting glucose (≥5.6 mmol/l) only in boys (1.18, 1.03 to 1.36). With these binary outcomes there was statistical evidence that associations differed between girls and boys for fasting glucose (P=0.03) and insulin (P<0.001). When risk factors were examined as continuous outcomes there was evidence for stronger associations of BMI with more adverse levels in boys than girls for fasting insulin, glucose, and triglyceride concentrations (all interaction P≤0.03). BMI, waist circumference, and fat mass were all strongly correlated with each other ( r =0.89-0.94), and associations of the three with cardiovascular outcomes were of similar magnitude with statistical evidence of consistency in associations (all P>0.2 for heterogeneity). When waist circumference or fat mass or both were added to models including BMI they did not increase the variation in cardiovascular risk factors already explained by BMI and confounders alone. Girls who were overweight/obese at age 9-12 but were normal weight by 15-16 had similar odds of adverse levels of risk factors to those who were normal weight at both ages. In boys odds of high systolic blood pressure, high concentrations of triglycerides and insulin, and low concentrations of high density lipoprotein cholesterol remained higher in this group compared with those who were normal weight at both ages but were lower than in those who remained overweight/obese at both ages. Conclusions Measurements of waist circumference or directly assessed fat mass in childhood do not seem to be associated with cardiovascular risk factors in adolescence any more strongly than BMI. Girls who favourably alter their overweight status between childhood and adolescence have cardiovascular risk profiles broadly similar to those who were normal weight at both time points, but boys who change from overweight to normal show risk factor profiles intermediate between those seen in boys who are normal weight at both ages or overweight at both ages.